Analisis Hukum Pidana terhadap Tindakan Catcalling : Upaya Memberantas Budaya Pelecehan Seksual di Ruang Publik - Dhea Salsa Fadhila; Helida Alfatarin Edib Hanum; Rahma Rini Khalisa Firdausi; Najwa Alya Ristiani; Chammellia Annastasya Melati; Thaasafina Sitasari Putri (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
Sexual harassment is a behavior with sexual connotations that is done without the consent of the intended person, including various forms such as physical, verbal, and non-verbal. In Indonesia, verbal sexual harassment such as catcalling is common but less recognized by society. Catcalling, which is often directed at women, is often considered trivial and not seen as a form of criminal offense. In fact, this act can have a serious psychological and emotional impact on the victim. Although there is still a lack of understanding about the Sexual Violence Law, it is hoped that this law can provide legal protection for victims. The Criminal Code (KUHP) also regulates crimes of decency, but non-physical sexual harassment has not been specifically regulated, making law enforcement difficult. The problem of lack of legal awareness and the lack of regulations related to verbal sexual harassment are the main obstacles in providing protection to victims. From the above problems, the formulation of the problem to be sought is how the implementation of the law against the perpetrators of catcalling and whether the criminal law in Indonesia has been good enough in dealing with the criminal act of catcalling as a form of sexual harassment. This research was conducted using qualitative methods and inductive research, and research using deductive methods, and using an empirical juridical approach.